The Prevalence and burden of malaria, soil-transmitted helminths, Schistosomiasis and their co-occurrence among school children in Ogun State - Kehinde Amoo; Abimbola Amoo; Adewale Oke; Olusola Ojurongbe; Jerome Ajewole; Iyanuoluwa Abioye; Oluwakunmi Lawal (Babcock University Medical Journal, 2025)
Objectives: Untreated malaria presents severe complications. Soil-transmitted helminths (STHs) of the trio Hookworm, Ascaris and Whipworm account for a major disease burden worldwide. While the health of school-aged children is usually compromised by common diseases such as malaria, helminthiasis and Schistosomiasis, the co-infections are accountable for increased morbidities and associated consequences like anaemia and malnutrition in vulnerable populations. The study determined the prevalence and burden of polyparasitism with these 3 diseases among school children in the study areas.